The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s0100-83582009000500001
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento da infestação de plantas aquáticas em Porto Primavera antes do enchimento final do reservatório

Abstract: O objetivo deste trabalho foi identificar as plantas aquáticas e os níveis de infestação de cada espécie em Porto Primavera antes do enchimento final do reservatório. Foram avaliados todos os focos de vegetação aquática no reservatório (72 pontos), sendo os pontos demarcados com um aparelho de GPS. As espécies foram identificadas e estimouse visualmente (tamanho da área) a distribuição proporcional das plantas no foco de infestação. Após a identificação, foram encontradas 18 espécies de plantas aquáticas veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
2
0
9
Order By: Relevance
“…A proliferação desequilibrada de determinadas plantas aquáticas em reservató-rios de hidrelétricas causa graves prejuízos ambientais e econômicos para a sociedade, entre os quais problemas como competição e substituição de espécies nativas, geração de energia, navegação, pesca, prática de esportes náuticos, proliferação de insetos e doenças (Carvalho et al, 2003;Martins et al, 2008Martins et al, , 2009Martins et al, , 2011.…”
Section: Introductionunclassified
“…A proliferação desequilibrada de determinadas plantas aquáticas em reservató-rios de hidrelétricas causa graves prejuízos ambientais e econômicos para a sociedade, entre os quais problemas como competição e substituição de espécies nativas, geração de energia, navegação, pesca, prática de esportes náuticos, proliferação de insetos e doenças (Carvalho et al, 2003;Martins et al, 2008Martins et al, , 2009Martins et al, , 2011.…”
Section: Introductionunclassified
“…Due to the unpredictable growth shown by aquatic plants in reservoirs, several studies have been carried out to understand their biology and distribution as along with alternative control methods to find more appropriate management of these plants (Bini et al, 1999;Martins et al, 2009). One of these studies identified 39 species belonging to 21 families found in five hydrographic basins of the state of São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Some aquatic plants, such as the native species Egeria densa (Planch.) Casp and E. najas Planchon (both Hydrocaritaceae), previously restricted to riverine margins and pools, have multiplied rapidly in Jupiá Lake and become 'nuisance' plants (Getsinger and Dillon, 1984;Haramoto and Ikusima, 1988;Mori et al, 1999;Oliveira et al, 2005;Martins et al,2009).…”
Section: Introductionmentioning
confidence: 99%